Ensayo sobre la realidad socioecológica : no alcanza para todos - Borner, Joachim (Universidad Academia de Humanismo Cristiano, 2018)
The essay starts of with a personal reflection of a senior researcher who has been investigating on global environmental change since the early beginnings of his career. It then moves to an analysis of the present challenges of humanity and the predominant narratives, which seem to steer our actions and hinder us from mitigating climate change and for staying within the planetary boundaries. Also it points out the role of hyperobjects, such as climate change, which are too big to grasp and too abstract to feel or imagine. In the discussion it opens up the imperative of creating new narratives to tackle the above issues, and reflects on the role of storytelling / future narrations to reach this goal of utmost importance for our planet's - for humanity's sake.